Evaluation of Supermicrosurgical Lymphatico-Venular Anastomosis By Means of Lymphoscintigraphy: Preliminary Results in 23 Patients - Yapici, O.; Demirtas, Y.; Aydin, Mahmut; Ozturk, N.; Basoglu, T. (Springer, 2008)
…